Code of Ethics Political Prospects of Economic Law in Legislation - Nursyamsudin, Febriyana; Ali Rasyid, Fauzan; Saleh, Chaerul (Zona Law And Public Administration Indonesia, 2024)
The legal system in economics related to the national consensus on welfare is quite complex due to the existence of various legal and political analyses. This research focuses on economic and legal domains related to Indonesia's economic challenges. One thing that is important in politics is the importance of ethics and morality. Ethical considerations of government tend to operate more efficiently. When government officials have strong moral convictions, they take action and defend their integrity. This undermines honesty, integrity, and good judgment when performing government functions. In order to realize the goals of the country, professional and ethical state administrators are needed in order to carry out their functions and duties efficiently and effectively. To realize a professional state administrator, each state administrator must meet the requirements as a state administrator as specified in laws and regulations, while to realize an ethical state administrator, it is necessary to regulate ethics in laws and regulations. The arrangement must be general in nature so that it applies to every state administrator.